The Studio PANaroma and Electroacoustic Music in Brazil - Menezes, Flo [UNESP] (MIT Press, 2022)
This article discusses the foundation of Studio PANaroma de Música Eletroacústica in São Paulo in 1994, an institution of the São Paulo State University and one of the most active research and production centers in the area in the world, contextualizing its conception with the internationalist tendencies present since the beginning of modernism in Brazil. To this end, the text discusses the notion of cultural anthropophagy, as formulated by Oswald de Andrade; discusses a brief history of the first initiatives in the field of electroacoustic music in Brazil; and focuses on the historical importance and the particularity of the Studio PANaroma, which substantially changed the development of electroacoustic music in the country. The studio’s activities are described, including the founding of the studio’s loudspeaker orchestra, as well as the studio’s main research activities.